Pedagogical thinking and scholar arithmetic for elementary course in Brazil and Spain. Times for intuitive training - Wagner RODRIGUES VALENTE (Ediciones Universidad de Salamanca, 2013)
This text analyses the raising of pedagogical thinking on the intuitive teaching of Arithmetic in primary school in Brazil and Spain. In order to do so, the appropriation of Pestalozzi's ideas is discussed, from the new historiography tendency of trying to resume a global history by comparative studies. In this way, the aim of this study is to answer the question: How had the ideas of teaching arithmetic being altered in these two countries in the early grades from the intuitive perspective?